Agritourism - Sznajder, Michal; Przezborska, Lucyna; Scrimgeour, Frank (CABI Publishing, 2009)
Describes the activity of holidaymaking in rural areas, specifically for those seeking a rural experience. The authors present the depth and variety of agritourim practiced around the world and cover various aspects of the economics and organization of agritourism. It discusses topics such as agricultural economics, marketing, and rural policy.